EFEKTIVITAS PROGRAM KARTU PRAKERJA BAGI FRESH GRADUATE DI KOTA MANADO - Ondang, Gilbert Luis; Mingkid, Elfie; Tasik, Femmy C. M. (Sam Ratulangi University, 2022)
This study aims to analyze the effectiveness of the pre-employment card program for fresh graduates in Manado City. This research was conducted from November 2021 to February 2022. This type of research used descriptive qualitative methods. The results showed that the pre-employment card program did not run effectively and optimally. This is because the program is not running on target, the data verification and control process is not accurate and up to date so that participants who are not actually included in the requirements can pass and receive incentives. In addition, the socialization process by the North Sulawesi Province Manpower and Transmigration Office was not optimal and only relied on socialization from the central Pre-Employment Implementing Team and Management. The tendency of participants is only on incentives. Incentives are only used for daily needs and lead to consumptive behavior. The certificate of training results does not guarantee participants to easily get a job. The training is only in the form of videos and is not given live. The lack of control and supervision affects the level of discipline of the participants. There is no room for interaction and discussion when there are participants who do not understand the training material. The absence of continuous assistance to participants causes this program to not show satisfactory results. Based on the results of this study, it can be concluded that the pre-employment card program for fresh graduates in Manado City is not running effectively and does not show maximum results. So it is necessary to evaluate and improve management regularly and continuously, starting from the data verification process, socialization, program implementation results, as well as in program monitoring.